Povezava med Eysenckovimi osebnostnimi potezami in spominsko obnovo - Areh, Igor (Psihološka obzorja (Ljubljana), 2008)
The research examines the efficiency of episodic memory in the context of eyewitness memory. The purpose of the research was to ascertain the connection between personality traits and memory recall, what may allow us to form a model of reliability prediction of eyewitness testimony. It was hypothesized that high neuroticism, psychoticism and high introversion are connected with low accuracy and quantity of memory recall. Participants were undergraduate students (N = 280) between the ages of 18 and 21. Personality traits were measured by Eysencks' Personality Questionnaire (EPQ). After the application of questionnaire a video about a robbery assault on a female was shown. Seven days later the accuracy and quantity of memory recall were tested with an extensive checklist. It was established that extraversion is not correlated with memory recall in men, while in females a positive correlation was found. Among females, high neuroticism was correlated negatively with the accuracy and quantity of memory recall, and in men only a negative correlation with quantity of memory recall was found. All correlation coefficients were weak, therefore it was impossible to form an applicable model of reliability prediction of eyewitness testimony. The main weakness of the research presented was the sample anomaly, which was evident in noticeable deviation in the average level of extraversion when it was compared with the expected standard for the Slovenian population.
Keywords: osebnostne lastnosti; vprašalniki; Eysenckov vprašalnik osebnosti (EPQ-R); memory; spomin; psihologija; psychology